System strategy to achieve full-face aesthetic with hyaluronic acid fillers: Yes-lifting and pyramid-volumized approaches - Yu-Pin Peng; Yi-Wen Lin; Yu-Yen Yang (Elsevier, 2022)
Individualized strategies are becoming critical for full-face aesthetics, especially for rejuvenating the aging face. This study aimed to assess the clinical outcomes following the Yes-lifting and Pyramid-volumized approaches with hyaluronic acid (HA) fillers. The Yes-lifting and Pyramid-volumized approaches represent the author's clinical experience of facial contouring techniques. The Yes-lifting method focuses on lifting the full-face using sharp needles to inject an appropriate volume of HA at 9 different positions, while the Pyramid-volumized method mainly refills the soft tissue with HA through a blunt cannula at 8 areas. These techniques are chosen based on patients' needs. After Yes-lifting treatment, the patient had an appreciable change to the face, which included lateral structural changes of the full-face and the support of deep malar fat pads. The oblique view exhibits improved zygomatic arch, a nicer jaw angle and chin-elongation and a more defined jawline. For another patient treated with the Pyramid-volumized approach, the facial shape improved immediately after treatment, with improvements in the bitemporal, bizygomatic, binasolabial fold, diminished T-troughs and chin. With pyramid-volumizing strategy, the patient looked more confident due to lateral structural changes of the full-face and the support of deep malar fat pads. The oblique view exhibits improved zygomatic arch, a nicer jaw angle, highlighted lips and a more defined jawline. Based on our experiences using the Yes-lifting or Pyramid-volumized technique can effectively improve aesthetic outcomes and provide a platform for user-friendly algorithms to help clinicians perform the facial contouring techniques, particularly for the Asian population.